GLCCI1 variant accelerates pulmonary function decline in patients with asthma receiving inhaled corticosteroids. Issue 5 (27th March 2014) - Izuhara, Y.; Matsumoto, H.; Kanemitsu, Y.; Izuhara, K.; Tohda, Y.; Horiguchi, T.; Kita, H.; Kuwabara, K.; Tomii, K.; Otsuka, K.; Fujimura, M.; Ohkura, N.; et al.
Abstract Background In steroid‐naive patients with asthma, several gene variants are associated with a short‐term response to inhaled corticosteroid (ICS) treatment; this has mostly been observed in Caucasians. However, not many studies have been conducted for other ethnicities. Here, we aimed to determine the relationship between the annual decline in forced expiratory flow volume in one second (FEV1) and the variant of the glucocorticoid‐induced transcript 1 gene (GLCCI1) in Japanese patients with asthma receiving long‐term ICS treatment, taking into account the effect of high serum periostin levels, a known association factor of pulmonary function decline and a marker of refractory eosinophilic/Th2 inflammation. Methods In this study, 224 patients with asthma receiving ICS treatment for at least 4 years were enrolled. The effects of single‐nucleotide polymorphisms (SNPs) in GLCCI1, stress‐induced phosphoprotein 1 (STIP1), and Tgene on the decline in FEV1 of 30 ml/year or greater were determined. Results Besides the known contributing factors, that is, the most intensive treatment step, ex‐smoking, and high serum periostin levels (≥95 ng/ml), the GG genotype of GLCCI1 rs37973, and not other SNPs, was independently associated with a decline in FEV1 of 30 ml/year or greater. When patients were stratified according to their serum periostin levels, the GG genotype of rs37973 was significantly associated with blood eosinophilia (≥250/μl) in the high serum periostin group. Conclusions A GLCCI1 variant is a risk factor of pulmonary function decline in Japanese patients with asthma receiving long‐term ICS treatment. Thus, GLCCI1 may be associated with response to ICS across ethnicities.